2011
DOI: 10.1038/ki.2011.223
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular disease in chronic kidney disease. A clinical update from Kidney Disease: Improving Global Outcomes (KDIGO)

Abstract: Cardiovascular morbidity and mortality in patients with chronic kidney disease (CKD) is high, and the presence of CKD worsens outcomes of cardiovascular disease (CVD). CKD is associated with specific risk factors. Emerging evidence indicates that the pathology and manifestation of CVD differ in the presence of CKD. During a clinical update conference convened by the Kidney Disease: Improving Global Outcomes (KDIGO), an international group of experts defined the current state of knowledge and the implications f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
576
3
37

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 787 publications
(638 citation statements)
references
References 207 publications
5
576
3
37
Order By: Relevance
“…4,12,21 Indeed, a diagnosis of CAD might be problematic in the setting of CKD, since such patients frequently do not experience ischemic symptoms, elevated cardiac biomarkers, and ECG changes. 3,4,22 Although coronary angiography has been considered the gold standard for detecting CAD, contrast media-induced nephropathy or cholesterol microembolization has emerged as serious problems. 9 Figure 2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,12,21 Indeed, a diagnosis of CAD might be problematic in the setting of CKD, since such patients frequently do not experience ischemic symptoms, elevated cardiac biomarkers, and ECG changes. 3,4,22 Although coronary angiography has been considered the gold standard for detecting CAD, contrast media-induced nephropathy or cholesterol microembolization has emerged as serious problems. 9 Figure 2.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Several studies have shown that the adjusted hazard ratio for death and cardiovascular events increases inversely with estimated glomerular filtration rates (eGFR). 1,2 An estimated 13% of the Japanese adult population has CKD.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with CKD have accelerated atherosclerosis and an increased risk of myocardial infarction, with cardiovascular disease remaining the most common cause of death 3. Based on previous seminal studies,4, 5, 6 the 2014 American College of Cardiology/American Heart Association (ACC/AHA) and the 2015 European Society of Cardiology guidelines recommend an urgent invasive strategy in high‐risk patients presenting with non–ST‐segment–elevation myocardial infarction (NSTEMI) 7, 8.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, subgroup analyses have revealed that the noise-attributed increase in BP was somewhat higher in CVD and diabetic patients in comparison to the rest. 13,19 Although the decline in renal function increases the risk of CVD morbidity and mortality 20 , there are no data on its relationship with RTN. One previous study, however, reported signifi cantly lower glomerular fi ltration rate in stroke survivors who lived within 50 m of a major road.…”
Section: Introductionmentioning
confidence: 99%